Teaching BIPA (Bahasa Indonesia Untuk Penutur Asing) for Sudanese; Lesson Learned in Bridging Indonesia and Sudan - Muhammad Ridwan (Hasanuddin University, 2016)
Teaching BIPA is one of the programs conducted by Badan Bahasa (Language Body) The Ministry of Education and Culture. The Ministry holds BIPA class both in many language centers of universities in Indonesia and in Indonesian Embassy offices abroad or universities. For instance in Sudan. BIPA class was taught at Indonesian Embassy Office in downtown Khartoum, the capital of Republic of Sudan. This paper aims to describe lesson learned obtained during the implementation. This includes best practices and challenges. Furthermore, In Sudan particularly, teaching BIPA has been conducted prior to DIKTI innitiatives. Both Embassy staff and Indonesian students working as Staff Assistant at the embassy involved in the program. This innitiatives should be sustainable to more internationalize our Bahasa Indonesia around the globe.